Transformasi Kebijakan Fiskal Berbasis Syariah : Mendorong Keadilan Sosial dan Pertumbuhan Inklusif di Indonesia - Putri Ayu Manalu; Nazwa Tantri Fitria; Ahmad Wahyudi Zein (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the framework of Islamic economics, which places a strong emphasis on social justice and ethics, fiscal policy is crucial in controlling a nation's economy. The necessity to comprehend how fiscal policy can be executed in line with sharia principles in order to attain public welfare serves as the backdrop for this study. This study's goal is to investigate the connection between Islamic economics and fiscal policy and evaluate how it affects the general welfare. The approach is library research, which involves gathering and examining a variety of works pertaining to Islamic economics' fiscal policy. The findings demonstrate how fiscal policies rooted in Islamic principles, like zakat and charity, can promote equitable and inclusive economic growth. In the Islamic system, fiscal policy fosters social and spiritual peace in addition to financial welfare. To sum up, fiscal policies that adhere to sharia principles can establish a just, durable, and advantageous economic structure that benefits all societal levels. Therefore, in order to attain economic stability and overall welfare, it is crucial that the government execute fiscal policies that are consistent with Islamic beliefs.